Stereoselectivity ratios in a simple Diels-Alder reaction in aqueous salt solutions of alcohols - Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron, 2005)
This is the first exhaustive report on the variation of stereoselectivity ratios for a simple Diels-Alder reaction between cyclopentadiene and methyl acrylate. The reaction was carried out in aqueous mixtures of methanol, ethanol, propan-1-ol and butan-1-ol in presence of LiClO4, LiCl, NaCl, KCl, CaCl2 and MgCl2. The endo sterecisomer decreases with the increase in carbon chain length of the alcohol. However, LiClO4, a salting-in agent in water becomes salting-out in aqueous mixtures of alcohols. The solvent properties, thus can be attuned by adjusting the amount of solvents and salts. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: aqueous alcohols; Diels-Alder reaction; endolexo ratios; salts